Colloidal Synthesis of Ternary AgFeS2 Nanocrystals and Their Transformation to Ag2S‐Fe7S8 Heterodimers. Issue 22 (5th May 2013) - Han, Shi‐Kui; Gu, Chao; Gong, Ming; Wang, Ze‐Ming; Yu, Shu‐Hong
<x xml:space="preserve">Abstract</x> Ternary‐/hetero‐nanocrystals: a facile one‐pot colloidal route for controlled synthesis of ternary AgFeS2 nanocrystals, which have a band gap of 1.21 eV, is presented for the first time. Such ternary AgFeS2 nanocrystals can transform to Ag2S‐Fe7S8 heterodimers by internal thermal reaction at elevated temperature, providing a new route to synthesize semiconductor hetero‐nanostructures. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>